Problématiques de l'imaginaire du Nord en littérature, cinéma et arts visuels - Bouchard, Joë; Chartier, Daniel; Nadeau, Amélie (Département d'études littéraires, UQÀM, 2004)
Conçu comme un discours et non comme un simple référent géographique, le Nord se déploie dans des formes littéraires et culturelles qui en déterminent les particularités. Pluriculturel, variable selon les époques, les lieux et les points de vue, le Nord ouvre des problématiques sur les liens entre le référent et la représentation, entre le discours et l'imaginaire. Qu'il soit scandinave, québécois, finlandais, inuit ou européen, qu'il se manifeste dans les récits, les films, les romans, la poésie, la photographie ou les arts visuels, qu'il soit le lieu d'une dénonciation post-coloniale ou d'un discours impérialiste, d'une recherche formelle ou de l'expression de la culture populaire, le discours du Nord et sur le Nord converge en des paradigmes et des problématiques qui lui sont propres. Dans ce recueil, issu des travaux du Laboratoire international d'étude multidisciplinaire comparée des représentations du Nord et initié par la tenue d'un colloque organisé en décembre 2003 par Joël Bouchard et Amélie Nadeau, le lecteur trouvera quelques pistes d'analyse pour saisir la complexité du système discursif du Nord, réparties en trois sections intitulées: «Formes et intertextualité», «Territoires», ainsi que «Iconographie, voyages, et cinéma».
Section: 171 p. : ill. ; $c 21 cm.
Keywords: 2-Épistémologies autochtones; 2-Étude des représentations; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Autrice; _Nettoyé; _À analyser; _À nettoyer; _À vérifier-Cinéma; _À vérifier-Histoire de l'art; _À vérifier-Télé

“We All Stand Side by Side”: An Interview with Elizabeth LaPensée - Hearne, Joanna (Studies in American Indian Literatures, 2017)
Keywords: 2-Épistémologies autochtones; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Autrice; 5-Créateur.rice autochtone; 5-Créatrice; _Nettoyé; _À analyser; _À nettoyer; _À vérifier-Histoire de l'art

Coming to You from the Indigenous Future: Native Women, Speculative Film Shorts, and the Art of the Possible - Medak-Saltzman, Danika (Studies in American Indian Literatures, 2017)
Keywords: 2-Épistémologies autochtones; 3-Amérique du Nord (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); _Nettoyé; _À analyser; _À nettoyer; _À vérifier-Cinéma; _À vérifier-Histoire de l'art; _À vérifier-Télé

Looking for Leroy: Illegible Black Masculinities - Neal, Mark Anthony (New York University Press, 2013)
Mark Anthony Neal’s Looking for Leroy is an engaging and provocative analysis of the complex ways in which black masculinity has been read and misread through contemporary American popular culture. Neal argues that black men and boys are bound, in profound ways, to and by their legibility. The most “legible” black male bodies are often rendered as criminal, bodies in need of policing and containment. Ironically, Neal argues, this sort of legibility brings welcome relief to white America, providing easily identifiable images of black men in an era defined by shifts in racial, sexual, and gendered identities. Neal highlights the radical potential of rendering legible black male bodies—those bodies that are all too real for us—as illegible, while simultaneously rendering illegible black male bodies—those versions of black masculinity that we can’t believe are real—as legible. In examining figures such as hip-hop entrepreneur and artist Jay-Z, R&B Svengali R. Kelly, the late vocalist Luther Vandross, and characters from the hit HBO series The Wire, among others, Neal demonstrates how distinct representations of black masculinity can break the links in the public imagination that create antagonism toward black men. Looking for Leroy features close readings of contemporary black masculinity and popular culture, highlighting both the complexity and accessibility of black men and boys through visual and sonic cues within American culture, media, and public policy. By rendering legible the illegible, Neal maps the range of identifications and anxieties that have marked the performance and reception of post-Civil Rights era African American masculinity.
Google-Books-ID: sKRFmvIVcEIC
Keywords: 2-Étude des industries culturelles; 2-Étude des représentations; 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Auteur.rice noir.e; _Nettoyé; _À analyser; _À nettoyer; _À vérifier-Cinéma; _À vérifier-Histoire de l'art; _À vérifier-Télé

The Transatlantic Zombie: Slavery, Rebellion, and Living Death - Lauro, Sarah Juliet. (Rutgers University Press, 2015)
Our most modern monster and perhaps our most American, the zombie that is so prevalent in popular culture today has its roots in African soul capture mythologies. The Transatlantic Zombie provides a more complete history of the zombie than has ever been told, explaining how the myth's migration to the New World was facilitated by the transatlantic slave trade, and reveals the real-world import of storytelling, reminding us of the power of myths and mythmaking, and the high stakes of appropriation and homage. Beginning with an account of a probable ancestor of the zombie found in the Kongolese and Angolan regions of seventeenth-century Africa and ending with a description of the way, in contemporary culture, new media are used to facilitate zombie-themed events, Sarah Juliet Lauro plots the zombie's cultural significance through Caribbean literature, Haitian folklore, and American literature, film, and the visual arts. The zombie entered US consciousness through the American occupation of Haiti, the site of an eighteenth-century slave rebellion that became a war for independence, thus making the figuration of living death inseparable from its resonances with both slavery and rebellion. Lauro bridges African mythology and US mainstream culture by articulating the ethical complications of the zombie's invocation as a cultural conquest that was rebranded for the American cinema. As The Transatlantic Zombie shows, the zombie is not merely a bogeyman representing the ills of modern society, but a battleground over which a cultural war has been fought between the imperial urge to absorb exotic, threatening elements, and the originary, Afro-disaporic culture's preservation through a strategy of mythic combat
Keywords: 2-Histoire/Historiographie critique; 2-Étude des représentations; 4-Amérique du Nord (lieu de production du savoir); 5-Autrice; _Nettoyé; _À analyser; _À nettoyer; _À vérifier-Cinéma

Lyrical Nationalism: Gender, Friendship, and Excess in 1970s Hindi Cinema - Jha, Priya (The Velvet Light Trap, 2003)
In this essay I examine one particular feature of the films, the song-and-dance sequences, as they draw attention to the fractious nature of the postcolonial nation while simultaneously attempting to construct a space for the articulation of a consolidated national identity.
Keywords: 1-Cinéma; 2-Genre et sexualité; 2-Histoire/Historiographie critique; 2-Théories et épistémologie postcoloniales et décoloniales; 2-Étude des représentations; 3-Asie (corpus analysé); 4-Amérique du Nord (lieu de production du savoir); 5-Auteur.rice PANDC; 5-Autrice; 5-Identités diasporiques; _Nettoyé; _À analyser; _À nettoyer; _À vérifier-Cinéma